2020
DOI: 10.1148/ryct.2020200389
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Burden of COVID-19 Pneumonia at Chest CT Predicts Adverse Outcomes: A Post Hoc Analysis of a Prospective International Registry

Abstract: C oronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an unprecedented global health crisis with over 29.7 million confirmed cases worldwide as of September 17, 2020 (1). The most critical complication is acute respiratory failure requiring invasive mechanical ventilation, occurring in up to 17% of patients (2,3) which is associated with a high rate of in-hospital mortality (4,5). While the reversetranscription polymerase chain reaction (RT-PCR) assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
4
33
2
3
Order By: Relevance
“…Also, Tharakan et al reported that a significant increase was observed in mortality for every 0.5 °C increase in body temperature (34). In consistent with our study, Grodecki et al showed that consolidation in chest CT was associated with 3.4-fold increased risk for clinical deterioration (35).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Also, Tharakan et al reported that a significant increase was observed in mortality for every 0.5 °C increase in body temperature (34). In consistent with our study, Grodecki et al showed that consolidation in chest CT was associated with 3.4-fold increased risk for clinical deterioration (35).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“… 10 , 11 Furthermore, chest CT (irrespective of contrast medium administration) has been used to quantify disease burden. 12 , 13 …”
mentioning
confidence: 99%
“…Most of these studies focused on the radiological features of this novel disease [12][13][14][15][16][17], and the data are sparse with regard to the quantitative CT analysis. Several studies investigated the association between quantitative CT data and adverse clinical outcomes [18][19][20], but few related the dynamic change of these data with patients' clinical course.…”
Section: Discussionmentioning
confidence: 99%